Highly Oriented Electrospun P(VDF‐TrFE) Fibers via Mechanical Stretching for Wearable Motion Sensing. Issue 7 (21st May 2018) - Ma, Shaoyang; Ye, Tao; Zhang, Ting; Wang, Zhe; Li, Kaiwei; Chen, Ming; Zhang, Jing; Wang, Zhixun; Ramakrishna, Seeram; Wei, Lei
Abstract: Advances in functional fabrics enable the realization of wearable devices in the form factor of fibers that can be seamlessly adapted in our daily lives. For mechanical‐related sensing and power generation, piezoelectric materials are particularly favorable because they can convert mechanical shape changes into electric outputs. Electrospinning is a widely applied technique to produce extended length of fiber‐shaped piezoelectric devices. However, this versatile process normally results in randomly distributed fibers with poor electrical properties and limited response to mechanical stimuli. Here, a stretching‐induced alignment method is demonstrated to achieve highly oriented electrospun poly[(vinylidenefluoride‐ co ‐trifluoroethylene] P(VDF‐TrFE) fibers on a large scale. These globally aligned electrospun P(VDF‐TrFE) fibers exhibit an enhanced piezoelectric property and high mechanical endurance. Using this simple stretching method, a high average output voltage of 80% aligned electrospun P(VDF‐TrFE) fibers is 84.96 mV, about 266% of their original randomly distributed counterpart. Furthermore, when woven into an outfit, the aligned electrospun P(VDF‐TrFE) fiber bundle can work both individually and combined to monitor body gestures including angles of elbow bending and directions of a swinging arm, which may lead to the further development of motion‐tracking technology. Abstract : A stretching‐induced alignment method is demonstrated to achieve globally and highly oriented electrospun poly[(vinylidenefluoride‐ co ‐trifluoroethylene] (P(VDF‐TrFE)) nanofibers on a large scale. The resulting highly aligned nanofiber bundles are woven into a daily outfit for body motion sensing. The demonstration of monitoring body gestures including angles of elbow bending and directions of a swinging arm leads to the further development of motion‐tracking technology.